O uso da teoria da mutação constitucional pelo Supremo Tribunal Federal - Silva, Fábio Rodrigues da (2020)
The present work has as main object of studies the examination on the specific performance of the Supreme Federal Court, consisting in applying expressly in certain cases the theory of constitutional mutation, thus conceived as the informal process of changing the meaning of constitutional norms, without the suppression of the its text, in order to conform them to the new social realities and recognize new rights. We started from the hypothesis that the informal alteration of constitutional norms promoted by the Supreme Federal Court, in decisions in which the express and literal use of the theory of constitutional mutation was made, does not contribute to the achievement of a balanced and efficient justice, as it does not clear and objective criteria were used for the application of the aforementioned theory. The method used was the deductive and the research technique is documentary, bibliographic and jurisprudential, through the reading and conceptual review of the sources collected in books and scientific papers on the subject. The qualitative form of data collection was privileged, based on the analysis of specific judgments by the Federal Supreme Court. The idea is to reflect on the efficiency of Justice in promoting social justice because it combines the challenge of facing the weighting between the value of legal security with the paradigm of efficiency of Constitutional Jurisdiction, interrelating it to a specific judicial activity, whatever the application of the theory of constitutional change by the Federal Supreme Court in its judgments.